Optimization Design of Automatic Tea Ceremony Teacup Equipment Based on TRIZ Principle - Wang, Huayin; Sun, Wei; Chen, Dian; Xu, Xinyu; Cheng, Mohan; Gao, Yiwen (Transactions on Engineering and Technology Research, 2024)
With the development of science and technology and the accelerated pace of society, people are increasingly pursuing a convenient way of life. The art of making tea in traditional Chinese tea culture, although rich in deep cultural heritage, is difficult to adapt its cumbersome steps to the modern fast-paced life. In order to solve this contradiction, this paper applies TRIZ theory to optimize the design of fully automatic tea cup equipment, aiming to realize the automation of the tea brewing process, while retaining the cultural essence of traditional tea art. Through the automation design of the steps of blancher, tea brewing and aroma shaking, combined with modern mechanical design and intelligent control technology, this study proposes an innovative fully automatic tea ceremony teacup equipment program. The solution not only improves the efficiency of tea brewing, but also ensures the quality of tea soup and the experience of traditional tea ceremony through careful design. Ultimately, the feasibility and effectiveness of the proposed scheme are verified through kinematic analysis, prototype testing and user experience evaluation. This study is of great practical significance for the modernization and transformation of the traditional tea ceremony, and also provides a reference for the automation of other traditional processes.